Comparison between health-related quality of life in normal-weight and overweight-obese children. (30th September 2020) - Scrimaglia, S; Esposito, F; Masini, A; Marini, S; Gori, D; Toselli, S; Campa, F; Grigoletto, A; Messina, R; Dallolio, L
Abstract: Background: In Italy 32% of 6-10 aged children were overweight in 2017-2018. Measures of Health-Related Quality of Life (HRQoL) assess important aspects of health daily activities, physical symptoms, social interactions and emotional well-being. It is suggested that HRQoL is influenced by children's weight status. The aim of the study is to compare HRQoL among normal-underweight and overweight-obese children in an Italian sample. Methods: A cross-sectional study was conducted in 2019 among 144 children, aged 6-10, recruited in a primary school in Bologna (Italy). Children were divided in Group1 (G1: normal-underweight) and Group2 (G2: overweight-obese) using the International Obesity Task Force cut points. HRQoL was assessed using 4.0 Italian version of PedsQL questionnaire. We obtained summary scores for children's total HRQoL and two subscales: one for physical health and one for emotional, social and school functioning. Results: Of 144 children, 98 (68%) and 46 (32%) were respectively in G1 and G2. HRQoL total scores were 73.10±1.30 in G1 and 69.28±1.96 in G2 (p = 0.051). We analysed separately children in Grade 1 and Grade 3-4. In Grade 1, there were 68 children: 48 (71%) in G1 and 20 (29%) in G2. In grade 3-4 there were 76 children: 50 (66%) in G1 and 26 (34%) in G2. HRQoL total scores in grade 3-4 were: 73.28±1.63 in G1 and 72.66±2.32 in G2 (p = 0.41). In Grade 1, HRQoL total scores were 72.92±2.05 in G1 and 64.89±3.15 in G2 (p = 0.02); at subscale levels, means for physical health were 77.73±1.92 in G1 and 72.5±3.58 in G2 (p = 0.08) and means for emotional, social and school functioning were 70.35±2.48 in G1 and 60.83±4.04 in G2 (p = 0.02). Conclusions: The effects of child overweight and obesity on health-related QOL was more evident in children aged 6-7, especially regarding emotional, social and school functioning. Prevention of childhood overweight and obesity is important not only to avoid health consequences of weight but also to improve children' quality of life. Key messages: Overweight is a public health problem in Italy not only among adults, but even among children. Overweight has a negative impact on quality of life, therefore a healthy lifestyle should be promoted.